Propolis Extract Attenuates NF-κB Activation and Chronic Kidney Disease Progression in a Rat Model: Potential Surgical Adjuvant? - Aulia Agung Sanubari; Darmawan Ismail; Kristanto Yuli Yarsa (HM Publisher, 2025)
Background: Chronic kidney disease (CKD) is a global health concern often complicated by cardiovascular diseases like atherosclerosis. Both conditions share an inflammatory pathogenesis, with nuclear factor kappa B (NF-κB) playing a central role. Propolis, a natural bee product with anti-inflammatory properties, has shown potential in mitigating CKD progression. This study aimed to investigate the effects of propolis extract on NF-κB activation in a rat model of CKD, exploring its potential benefits as a surgical adjuvant. Methods: Male white rats (Rattus norvegicus) were divided into three groups: a control group, a CKD group, and a CKD+Propolis group receiving propolis extract (200 mg/kg body weight) daily for 20 days. CKD was induced using the unilateral ureteral obstruction (UUO) method. NF-κB levels were measured weekly using ELISA. Results: Propolis extract significantly reduced NF-κB levels in the CKD+Propolis group compared to the CKD group (p<0.05). This effect was consistently observed across all time points, indicating a sustained reduction in NF-κB activation with propolis treatment. Conclusion: Propolis extract effectively attenuates NF-κB activation in a rat model of CKD, suggesting its potential as an adjunctive therapy for CKD management, particularly in the context of surgical interventions. Further research is needed to elucidate the underlying mechanisms and evaluate its efficacy in human subjects.